Involvement of 14-3-3 Proteins in Regulating Tumor Progression of Hepatocellular Carcinoma - Wu, Yi-Ju (Cancers (Basel), 2015)
There are seven mammalian isoforms of the 14-3-3 protein, which regulate multiple cellular functions via interactions with phosphorylated partners. Increased expression of 14-3-3 proteins contributes to tumor progression of various malignancies. Several isoforms of 14-3-3 are overexpressed and associate with higher metastatic risks and poorer survival rates of hepatocellular carcinoma (HCC). 14-3-3β and 14-3-3ζ regulate HCC cell proliferation, tumor growth and chemosensitivity via modulating mitogen-activated protein kinase (MAPK), c-Jun N-terminal kinase (JNK) and p38 signal pathways. Moreover, 14-3-3ε suppresses E-cadherin and induces focal adhesion kinase (FAK) expression, thereby enhancing epithelial-mesenchymal transition (EMT) and HCC cell migration. 14-3-3ζ forms complexes with αB-crystallin, which induces EMT and is the cause of sorafenib resistance in HCC. Finally, a recent study has indicated that 14-3-3σ induces heat shock protein 70 (HSP70) expression, which increases HCC cell migration. These results suggest that selective 14-3-3 isoforms contribute to cell proliferation, EMT and cell migration of HCC by regulating distinct targets and signal pathways. Targeting 14-3-3 proteins together with specific downstream effectors therefore has potential to be therapeutic and prognostic factors of HCC. In this article, we will overview 14-3-3’s regulation of its downstream factors and contributions to HCC EMT, cell migration and proliferation.